Features on providing enterprise financial security in the Covid-19 pandemic - K. Oriekhova; O. Golovko; O. Khrystoforova; M. Efymenko (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Економіка, 2022)
COVID-19 pandemic conditions led to a number of risks for financial security on both macro and on macro levels. Since quarantine continues, the influence of risks on the financial security of Ukraine and business entities is significantly increased. The government has implemented a set of measures to prevent the dissemination of COVID-19 diseases on the territory of Ukraine. However, the dynamic movement of the epidemic situation, the negative consequences of the action of measures and the deployment of the global economic crisis require an operational response to the threats of financial security. In modern conditions, the introduction of legal and regulatory changes, state financial support and organizational and economic mechanisms are essential financial security tools. Special attention is required to determine the impact of crisis phenomena on the financial security of business entities of Ukraine. Risk accounting should be based on practical recommendations for reducing financial security threats, ensuring financial sustainability, meet financial needs and the protection of financial interests of both Ukraine and business entities. The article examines both the definition of the concept and the financial security system of business entities and the influence of state regulation on the processes of opposition to the dissemination of the Pandemic COVID-19, overcoming the consequences and prevention of bankruptcy and liquidation of business entities. For the period 2021-2024 The influence of the risks of the Pandemic of COVID-19 on the financial security of the Ukrainian economy and business entities are rated. This may be the main tool for ensuring financial security under the COVID-19 pandemic. The latest trends in the introduction of modern digital technologies, taking into account the risks of financial security on macro and on macro levels.